2017
DOI: 10.1016/j.resconrec.2017.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of element-specific recycling efficiency in WEEE pre-processing

Abstract: Pre-processing is a crucial step to ensure the efficiency of subsequent processes and the quality of recyclates. The efficiency of pre-processing can be affected by high losses to undesignated output fractions. Standard batch tests usually provide mass balances and are a good proxy for bulk materials balances (iron/steel, aluminum, plastics). This article aims at harmonizing methodologies and recommends a strategy for further study in pre-processing on a plant scale. We have developed an “extended batch test”… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(21 citation statements)
references
References 60 publications
0
21
0
Order By: Relevance
“…Indium concentrations in some finished goods are comparable with those in minerals, and in some cases they are even higher (figure ), but the huge variety and number of single products to be collected and processed have to face the issue of dispersion (Ueberschaar et al. ).…”
Section: Resultsmentioning
confidence: 99%
“…Indium concentrations in some finished goods are comparable with those in minerals, and in some cases they are even higher (figure ), but the huge variety and number of single products to be collected and processed have to face the issue of dispersion (Ueberschaar et al. ).…”
Section: Resultsmentioning
confidence: 99%
“…The total cost for europium recycling from spent lamps includes costs for collection at end-of-life and further processing for elemental recovery. In addition, the grade of europium recovered, reagent costs, energy consumption, inefficiency during end-of-life collection and sorting, mandatory recycling quotas based on the mass of product, and decreasing concentrations in products are limiting factors in the recovery efficiency process [10,47,60,65]. Second, the transition from fluorescent lamps to SSL technology is expected to make the demand for europium peak and then decline [66] because the quantities of REEs required per unit of SSL are up to some orders of magnitude lower than those needed to produce fluorescent lamps.…”
Section: Potentials For End-of-life Recovery and For Closing The Euromentioning
confidence: 99%
“…For efficient recycling of e-waste, pre-treatment as a combination of manual (dismantling and separation) and physical processes (size reduction and different physical separation) represent a first and indispensable step. The main task of WEEE pre-processing is to ensure that liberated materials enter the appropriate recovery processes (Ueberschaar et al, 2017a). Before final metal recovery in hydro and/or pyro metallurgical processing, appropriate pre-treatment steps, are crucial.…”
Section: Description Of Currently Applied Pre-treatment Processesmentioning
confidence: 99%
“…To improve the recovery of precious and other critical metals, it is essential to manually remove the components containing important raw materials such as PCBs and batteries and feed these components separately to recycling facilities. Based on elemental material flow analysis Ueberschaar et al (2017a), concluded that in pre-sorting step due to battery removal, about 46% of cobalt and 38% of a group of REEs are separated from the input WEEE flow. High concentrations of cobalt and REEs (about 30% and 60%, respectively) were also found within ferrous metals fraction after use of magnet separator (Figure 3).…”
Section: The Fate Of Cms In Pre-treatment Processesmentioning
confidence: 99%
See 1 more Smart Citation